A legal study in Malaysia on the right of children to decide their own religion under the law reform: Marriage and Divorce Act 1976 / Ahmad Raziff A Aziz ... [et al.] - A Aziz, Ahmad Raziff; Zulkefeli, Nuruaiesah; Kamaruddin, Fairuzatasya; Sujak Rafie, Roshdan; Aripin, Fatin Dalila (2010)
The legal system in Malaysia is a dual system, based on both English Common Law and Islamic Law. Civil Courts have jurisdiction over the majority of laws, including contracts, torts, property, crime and constitutional and administrative matters. The Syariah Courts which are established and regulated by the states, have jurisdiction over Islamic family law matters. Article 121 (A) of the Federal Constitution, introduced in 1988 by constitutional amendment, states that the civil courts have no jurisdiction in matters that fall within the Syariah court's jurisdiction. In general, the welfare of the child is the paramount consideration in Islamic custody cases throughout Southeast Asia. The mother or another female relative is generally presumed to be the best person to maintain custody of young children, while older children, those who have reached the age of mumaiyiz (discernment), are given a choice in some jurisdictions. For mother who have remarried or are converts to Islam, however custody may not be given to the mother even in the case of young children. These are landmark decisions that seek to finally resolve a host dilemma faced by the non converting spouse after the partner convert the children as well, seize the matrimonial properties, start a war for custody and religion of the children and seek to anull their civil law marriage in the Islamic court. The work includes a wide catalogue of footnotes and reference, which on the one hand provides the reader with an access to invaluable sources and on the other hand provides a researcher with invaluable leads for future research. This research perhaps can constitute a valuable contribution to Faculty of Law and would be a good reference to student and teacher alike.